1983
DOI: 10.1073/pnas.80.10.3111
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and [Leu]enkephalin are hydrolyzed by an enzyme in pig caudate synaptic membranes that is identical with the endopeptidase of kidney microvilli.

Abstract: The hydrolysis of [Leu]enkephalin and substance P by purified pig kidney endopeptidase (EC 3.4.24.11) and synaptic membranes prepared from pig caudate nuclei has been compared. The hydrolysis of an enkephalin analogue (Tyr-D-Ala-GlyPhe-Leu) at the Gly-Phe bond was completely inhibited by phosphoramidon. The IC50 concentration (8 nM) was similar to that reported for [Leu] Biochem. J. 203,[519][520][521][522]. Seven peptides were produced when substance P (Arg-Pro-Lys-Pro-Gln-Gln-Phe-Phe-GlyLeu-Met-NH2) was hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
187
0
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(198 citation statements)
references
References 20 publications
10
187
0
1
Order By: Relevance
“…The IC50 value of enkephalin in the presence of 1 /-,M of phosphoramiclon was not significantly different from that of 2 uM of phosphoramidon, but significantly lower than that of 0.1 /iM of phosphoramidon (Table 3). This indicated that the enkephalin hydrolyzing endopeptidase-24.11 in rat vas deferens was inhibited maximally with phos phoramidon at the final concentration of 1 riM, being consistent with the previous results obtained with guinea-pig ileum (1 ), mouse vas deferens (2), pig caudate synaptic membranes (12) and purified endopeptidase 24.11 from pig kidney (13).…”
Section: Resultssupporting
confidence: 81%
“…The IC50 value of enkephalin in the presence of 1 /-,M of phosphoramiclon was not significantly different from that of 2 uM of phosphoramidon, but significantly lower than that of 0.1 /iM of phosphoramidon (Table 3). This indicated that the enkephalin hydrolyzing endopeptidase-24.11 in rat vas deferens was inhibited maximally with phos phoramidon at the final concentration of 1 riM, being consistent with the previous results obtained with guinea-pig ileum (1 ), mouse vas deferens (2), pig caudate synaptic membranes (12) and purified endopeptidase 24.11 from pig kidney (13).…”
Section: Resultssupporting
confidence: 81%
“…peptidase inhibitors employed (dotted arrows). "Enkephalinase" has recently been reported to be identical with endopeptidase 24.11 (10).…”
mentioning
confidence: 99%
“…11 efficiently inactivates gastrin releasing peptide 10 by cleavage of the His8-Leu9 bond (Bunnett, Kobayashi, Orloff, Turner, Reeve & Walsh, 1985). This membrane-bound peptidase is present in many tissues but is concentrated particularly in the kidney microvilli (Matsas, Fulcher, Kenny & Turner, 1983).…”
Section: Discussionmentioning
confidence: 99%